1976
DOI: 10.1111/j.1476-5381.1976.tb07655.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Purine Derivatives on the Guinea‐pig Trachea and Their Interaction With Drugs That Block Adenosine Uptake

Abstract: I Adenosine, adenosine 5'-triphosphate (ATP), adenine, inosine and guanosine all caused concentration-dependent relaxations of guinea-pig tracheal smooth muscle in vitro. The relative potencies in descending order were: adenine > guanosine > inosine > adenosine > ATP 2 Responses to the purine compounds were unaffected by propranolol (1 jg/ml). 3 The spasmolytic potencies of adenosine and ATP were greatly enhanced in the presence of the adenosine uptake blocking drugs dipyridamole, hexobendine or Dilazep, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 25 publications
5
49
1
Order By: Relevance
“…In contrast, dipyridamole and hexobendine have been shown to potentiate the inhibitory effect of adenosine and adenine nucleotide in the heart, intestine and trachea (Stafford, 1966;Kolassa, Pfleger & Rummel, 1970; At arrow, theophylline 30 gM was added to the superfusion solution. Satchell et al, 1972;Coleman, 1976). Our previous experiments with guinea-pig ileum demonstrated that the inhibitory effect of adenosine on cholinergic nerves was specifically antagonized by theophylline and potentiated by dipyridamole and hexobendine.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, dipyridamole and hexobendine have been shown to potentiate the inhibitory effect of adenosine and adenine nucleotide in the heart, intestine and trachea (Stafford, 1966;Kolassa, Pfleger & Rummel, 1970; At arrow, theophylline 30 gM was added to the superfusion solution. Satchell et al, 1972;Coleman, 1976). Our previous experiments with guinea-pig ileum demonstrated that the inhibitory effect of adenosine on cholinergic nerves was specifically antagonized by theophylline and potentiated by dipyridamole and hexobendine.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to define the pharmacological activity of adenosine on human airways. There have been many in vitro studies to show that adenosine and its modified purine analogues are capable of relaxing gastrointestinal (Ally & Nakatsu, 1976), vascular (Herlihy et al, 1976) and tracheal (Coleman, 1976) smooth muscle preparations. However, in asthma, rather than showing a relaxant response adenosine is a powerful bronchoconstrictor.…”
Section: Discussionmentioning
confidence: 99%
“…If adenosine antagonism is relevant to theophylline's effect on the airways in asthma, then adenosine should be a bronchoconstrictor (Fredholm, 1980a). In animal isolated tracheal and bronchial airway preparations whose tone has been artificially increased, adenosine causes relaxa-0306-5251/83/0200-1610 $02.00 tion (Fredholm et al, 1979;Coleman, 1976;Farmer & Farrar, 1976) whereas, in preparations of guineapig trachea with normal intrinsic tone, adenosine causes a weak but consistent contraction (Fredholm et al, 1979;Advenier et al, 1982). To extend the observations to man, we have investigated the effect of adenosine and the related nucleoside, guanosine, on the airways of normal and asthmatic subjects in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine may produce both a slight contraction (at low concentrations) and a relaxation of guinea-pig tracheae in vitro (Coleman, 1976). Holroyde (1986) reported contractions to adenosine only in epithelium-denuded tracheal preparations.…”
Section: Agents Producing Mixed Effectsmentioning
confidence: 99%